Analisis Kebijakan Pengelolaan Sumber Mata Air Berkelanjutan Desa Pucung: Temuan dan Rekomendasi untuk Masa Depan - Purwanta; Kinen Milang Pramudita (Direktorat Pengabdian kepada Masyarakat, 2024)
Water is the most fundamental physiological need for humans and plays a crucial role in ensuring human survival and well-being. In Desa Pucung, the presence of water is vital in daily life, but the management of the water sources in this village is not sustainable. This article aims to analyze sustainable water source management policies in Pucung Village using a qualitative approach. Through observation, interviews, and literature review, several issues were identified, such as murky water quality during the rainy season, simple reservoir conditions, inefficient hose distribution, and unsustainable water usage. Consequently, several policies are recommended to improve water management in Desa Pucung, including establishing protection zones around water sources, improving water reservoir infrastructure, developing better water distribution plans, specifying community participation types more clearly, and implementing risk management at the village government level. Additionally, this article also highlights best practices from other areas, such as water purification processes before distribution to the community, construction of water distribution tanks in residential areas, and establishment of protection zones around water sources. By implementing these policies, it is hoped that Desa Pucung can achieve more effective and sustainable water management in line with the principles of sustainable development.